EXCLAIM - Novel Line Intensity Mapping on a Balloon Borne Telescope - Siddique, Faizah Karim (Proceedings of the Wisconsin Space Conference, 2023)
Line intensity mapping (LIM) is a new and cost-efficient technique to study different astrophysical processes within our universe. LIM measures the collective emission from all sources in a region of the sky at a particular frequency. Distinguishing the line emissions to different emission lines and redshifts is important for studying different astrophysical processes, such as star formation. The EXperiment for Cryogenic Large-Aperture Intensity Mapping (EXCLAIM) will be a balloon borne experiment that aims to study star formation by mapping the intensity of singly ionized carbon [CII], and carbon monoxide (CO) transition lines. Building high fidelity simulations is required to develop the analysis pipeline when data is available.